Patterns of Antihypertensive Medication Utilization Among Hypertensive Patients: A Review of Single-Therapy Practices in Outpatient Primary Healthcare Centers - Fendy Prasetyawan; Yuneka Saristiana; Faisal Akhmal Muslikh; Chandra Arifin; Abd Rofiq; Elsa Mahardika Putri; Anis Akhwan Dhafin (Paspama Institute, 2024)
Hypertension, often referred to as